Safety evaluation of FAD2 RNAi transgenic Brassica napus L. based on microbial diversity and metabonomic analysis - Qi, Yanting; Wang, Qiming; Xie, Qingxuan; Wu, Chuan; Xu, Minhui; Han, Shaofan; Zhou, Ting; Li, Juan; Xia, Libing; Li, Wai chin; Pan, Weisong (Frontiers in Plant Science, 2022)
Oleic acid desaturase (FAD2) is the key enzyme to produce polyunsaturated fatty acids in rapeseed (Brassica napus L), which is one of the main oil crops. RNA interference (RNAi) is an emerging technique that provides new chances for the generation of new traits in plants. In order to increase oleic acid content and reduce linoleic and linolenic acid content in rapeseed, we constructed the ihpRNA plant expression vector of FAD2 gene, and obtained transgenic plants for multiple generations by stable inheritance. In this study, third generation transgenic plants (T3), seventh generation transgenic plants (T7) and wild-type plants (WT) were used. The differences in microbial community diversity between transgenic plants and wild-type plants, and the up- and down-regulation of rhizosphere metabolites content were investigated. In conclusion, no significant harmful effects of transgenic rapeseed on the environment were found through the microbial community and metabolomics analysis. This work may provide an understanding of the impact of RNA interference on plant metabolites, and provide safety evaluation method of transgenic plants and reference for rapeseed breeding.